ALIGNMENT OF THE CONCEPT OF CUSTOMARY CRIMINAL LAW WITH THE CONCEPT OF RESTORATIVE JUSTICE IN NATIONAL CRIMINAL LAW - Siregar, M.A.; Ikhsan, Edi (Universitas Efarina, 2023)
Customary law has long been ignored by our society because we are too enthusiastic about the criminal and civil laws adopted since the Indonesian colonial era. Although so-called modern law cannot prevent the limitations of its application in various regions throughout Indonesia, customary law can actually be a considerable substitute. Theoretically, this can be formally implemented in various regions in Indonesia by fulfilling several criteria in accordance with the principles used by national law. A major change in the orientation of criminal law is a shift in the concept of justice, from justice based on retribution to justice that is restorative justice. The protection and restoration of the rights of victims and the wider community is considered as important as the punishment and/or rehabilitation of criminals. Based on the Police Regulation of the Republic of Indonesia No. 8 of 2021 concerning the Handling of Criminal Acts Based on Restorative Justice, the aim is to realize that the case resolution process is not only aimed at punishing or humiliating someone, but rather at trying to obtain the truth which is useful to help restore harmonious relationships. between perpetrators, victims and society. This is actually nothing new in the archipelago because the Indonesian people are already familiar with it in their customary law and its authority has recently been approved in statutory regulations.